PROBLEM BASED LEARNING MODEL IN PROBLEM-SOLVING ON THE SUBJECT OF ISLAMIC CULTURE HISTORY - Rahman, Kholilur; Setiawati, Lilis; Ummah, Vina Rohmatul; Aniati, Ana (International Conference on Humanity Education and Society (ICHES), 2023)
The problem-based learning paradigm assists students in identifying challenges in complex circumstances. Students in this model collaborate in groups to identify the skills needed to address challenges. The goal of this study was to assess students' problem-solving abilities while studying Islamic Cultural History (SKI) using the Problem-Based Learning (PBL) learning approach. In the form of an evaluation method, this study employs a quantitative approach. According to the findings of this study, students' problem-solving abilities in Islamic Cultural History (SKI) courses improved after utilizing the Problem-Based Learning (PBL) learning model vs before using the learning model. As a result, the Problem-Based Learning (PBL) learning model is being employed effectively to increase students' problem-solving abilities.